Treating Suicidality in College Counseling Centers: A Response to Polychronis. Issue 1 (2nd January 2017) - Pistorello, Jacqueline; Coyle, Trevor N.; Locey, Nadia Samad; Walloch, Joseph C.
ABSTRACT: This is a commentary on the article by Paul D. Polychronis, "Changes Across Three Editions of The Suicidal Patient: Clinical and Legal Standards of Care : Relevance to Counseling Centers, " published in this issue of the Journal of College Student Psychotherapy .